A concurrent optimization model for suppliers selection, tolerance and component allocation with fuzzy quality loss. Issue 1 (31st December 2016) - Rosyidi, Cucuk Nur; Murtisari, Rina; Jauhari, Wakhid Ahmad
Abstract: The aim of this paper is to develop an optimization model to optimally select suppliers and allocate components to the selected suppliers. The objectibve function of the model is to minimize purchasing cost and fuzzy quality loss. Using fuzzy quality loss, the assembly quality may be divided into several grades allowing the fuzziness in the resulted assembly tolerance. The model considers several constraints such as production capacity, assembly quality, and process and technological capability of the suppliers. A numerical example is given in this paper to show the implementation of the model. Sensitivity analysis is performed to determine the effect of process capability to the supplier selection, components allocation and total cost. The increase of process capability in one of the suppliers affects the selection and component allocation mainly when the process capability increase from 1 to 1.5. Further, increasing the process capability index to 2 has no effect on the selection and allocation but affects the fuzzy quality loss and hence reduces the total cost.